Early Positive Approaches to Support (E-PAtS) for Families of Young Children With Intellectual Disability: A Feasibility Randomised Controlled Trial - Coulman, Elinor; Gore, Nick; Moody, Gwenllian; Wright, Melissa; Segrott, Jeremy; Gillespie, David; Petrou, Stavros; Lugg-Widger, Fiona; Kim, Sungwook; Bradshaw, Jill; McNamara, Rachel; Jahoda, Andrew; et al. (Frontiers in Psychiatry, 2021)
Background: Parents of children with intellectual disabilities are likely to experience poorer mental wellbeing and face challenges accessing support. Early Positive Approaches to Support (E-PAtS) is a group-based programme, co-produced with parents and professionals, based on existing research evidence and a developmental systems approach to support parental mental wellbeing. The aim of this study was to assess the feasibility of community service provider organisations delivering E-PAtS to parents/family caregivers of young children with intellectual disability, to inform a potential definitive randomised controlled trial of the effectiveness and cost-effectiveness of E-PAtS. Methods: This study was a feasibility cluster randomised controlled trial, with embedded process evaluation. Up to two parents/family caregivers of a child (18 months to less than 6 years old) with intellectual disability were recruited at research sites and allocated to intervention (E-PAtS and usual practice) or control (usual practice) on a 1:1 basis at cluster (family) level. Data were collected at baseline and three and 12 months’ post-randomisation. The following feasibility outcomes were assessed: participant recruitment rates and effectiveness of recruitment pathways; retention rates; intervention adherence and fidelity; service provider recruitment rates and willingness to participate in a future trial; barriers and facilitating factors for recruitment, engagement, and intervention delivery; and feasibility of collecting outcome measures. Results: Seventy-four families were randomised to intervention or control (n=37). Retention rates were 72% at 12 months post-randomisation, and completion of the proposed primary outcome measure (WEMWBS) was 51%. Recruitment of service provider organisations and facilitators was feasible and intervention implementation acceptable. Adherence to the intervention was 76% and the intervention was well-received by participants; exploratory analyses suggest that adherence and attendance may be associated with improved wellbeing. Health economic outcome measures were collected successfully and evidence indicates that linkage with routine data would be feasible in a future trial. Conclusions: The E-PAtS Feasibility RCT has demonstrated that the research design and methods of intervention implementation are generally feasible. Consideration of the limitations of this feasibility trial and any barriers to conducting a future definitive trial, do however, need to be considered by researchers.